The tyranny of experts : economists, dictators, and the forgotten rights of the poor - Easterly, William, 1957- (New York : Basic Books, a member of the Perseus Book Group, 2013)
Over the last century, global poverty has largely been viewed as a technical problem that merely requires the right "expert" solutions. Yet all too often, experts recommend solutions that fix immediate problems without addressing the systemic political factors that created them in the first place. Further, they produce an accidental collusion with "benevolent autocrats," leaving dictators with yet more power to violate the rights of the poor.
pt. 1. The debate that never happened. Introduction -- Two Nobel Laureates and the debate they never had -- pt. 2. Why the debate never happened : the real history of the development idea. Once upon a time in China -- Race, war, and the fate of Africa -- One day in Bogotá -- pt. 3. The blank slate versus learning from history. Values : the long struggle for individual rights -- Institutions : we oppress them if we can -- The majority dream -- pt. 4. Nations versus individuals. Homes or prisons? : Nations and migrations -- How much do nations matter? -- pt. 5. Conscious design versus spontaneous solutions. Markets : the association of problem-solvers -- Technology : how to succeed without knowing how -- Leaders : how we are seduced by benevolent autocrats -- Conclusion.
Includes bibliographical references (pages 355-380) and index.
Keywords: Economic policy -- Political aspects; Economic policy -- Social aspects -- Developing countries; Poverty -- Economic aspects -- Developing countries